For a dialectic of equality. Althusser’s antihumanism revision fifty years later (Delito y Sociedad, 2018)
This article considers the Althusserian thesis on Karl Marx’s anti-humanism from a theoretical, as well as a political, point of view. This leads us to the conceptualization of the contaminated difference between Theory and Politics, in the first case, and to the problem of the «value» of Democracy, in the second. Finally, recovering the hypothesis of the “erasure trace” as a clue to read the Althusserian concepts put forward by E. Balibar, we outline a “dialectics of equality” performed among three different topics of Althusser’s thought that should be acknowledged simultaneously: a «critique of inequality» focused on structural mechanisms that secure systemic reproduction, a «critique of equality as ideology», and the understanding of egalitarian discourse as inherent to emancipatory «political practices» implied as well in the (constitutively contaminated) language of critique.
Keywords: Althusser; Antihumanism; Theory; Democracy; Equality